Et fragment fra Grundtvig-arkivet - Albeck, Gustav (Grundtvig-Studier, 1991)
From the Grundtvig Archives Europe and America, or about the Imminent Change in State Relations (Fragment from 1820). By Gustav Albeck The fragment seems to be the beginning of a study (a review?), occasioned by C.F. von Schmidt-Phiseldeck’s book, "Europa und Amerika", oder die künftigen Verhältnisse der civilisierten Welt., which was published in the early summer of 1820. Grundtvig describes the book as .the strangest book that has been published in Denmark for a long time.. Its writer, who was German born, but became a Danish citizen already as a young man, held high posts in Danish government administration in the period from app. 1810 until his death in 1832 (e.g., in the College of Commerce and the National Bank), working at the same time as a writer of learned economic works as well as (more popular) philosophical writings. The book about Europe and America has been written from the writer’s conviction that the changed Europe (after the conclusion of the Napoleonic Wars) was going to loose her numerous colonies beyond the Atlantic Ocean and become weak and poor, whereas America (esp. the United States) would acquire increasing influence and wealth at the cost of the Old World. Grundtvig characterizes the dominant position of America as a matter of minor importance, and seems to want first of all to make his countrymen familiar with the thought that the European .State Household. is approaching a .Crisis., and to warn the apathetic Danes against the consequences of that crisis. The commentary on the fragment refers briefly to the - surprisingly few - passages in Grundtvig’s writings where he shows his view of America’s mission and place in world history. In .The World Chronicle., 1812, he describes Columbus as .a great Tool in God’s Hand, but adds that it was Columbus’ good fortune that the new continent ... did not come to bear his name.. This paradoxical attitude is noticeable wherever Grundtvig mentions America. The criticism is, in particular, directed against South America, whereas he often commends North America, esp. the .Free States. as a home of freedom. But Grundtvig has many difficulties in accepting the people of the American states, this peculiar motley crowd. (as he calls the immigrants in 1812), as a people created by God. In the 10th chapter of his book, Schmidt-Phiseldeck proposes the idea of a union of the states of Europe, a thought which he elaborated in detail in a subsequent volume, “Der europäische Bund”. If Grundtvig had finished his review, he would probably have rejected the idea of a union as early as 1820. At any rate, in the 1830s, he objects sharply to the Vienna Congress and its heavyhanded division of the European peoples, irrespective of their ethnic, national and cultural affiliations. He describes his view of these events, partly in his “Handbook of World History” (1833 sq), partly in the lectures he gave at Borch’s Kollegium in 1838 (which his son, Sven Grundtvig published in 1877 under the title .Within Living Memory. (“Mands Minde”)). There may be two explanations why Grundtvig did not finish his review in 1820. His intention seems primarily to draw attention to Schmidt-Phiseldeck’s book, but already in July 1820, A.C. Gierlew began work on a highly detailed, critical review, which appeared in 6 numbers of Dansk Litteratur-Tidende (Danish Literary News). At the same time a Danish translation of Schmidt-Phiseldeck’s book (by D. Didrichsen and H.A. Mortensen) was published, so that Grundtvig’s primary object was achieved. Another explanation why Grundtvig did not finish the article he had begun to work on, may be that in the summer of 1820, he felt tired and unfit for work, as it appears from his letter of September 9th, 1820, to his friend Christen Olesen.